The CDK12–BRCA1 signaling axis mediates dinaciclib‐associated radiosensitivity through p53‐mediated cellular senescence - Natalia García Flores; Diego M. Fernández‐Aroca; Cristina Garnés‐García; Andrés Domínguez‐Calvo; Jaime Jiménez‐Suárez; Sebastià Sabater; Pablo Fernández‐Aroca; Ignacio Andrés; Francisco J. Cimas; Guillermo deCárcer; Borja Belandia; Ignacio Palmero; et al. (Molecular Oncology)
Pan‐cyclin‐dependent‐kinase (CDK) inhibitors are a new class of targeted therapies that can act on multiple CDKs, with dinaciclib being one of the most promising compounds. Although used as a monotherapy, an interesting approach could be to combine it with radiotherapy. Here, we show that dinaciclib increases radiosensitivity in some experimental models of lung and colon cancer (A549 or HCT 116) but not in others (H1299 or HT‐29). Dinaciclib did not alter serine‐protein kinase ATM signalling or cell cycle profiling after ionising‐radiation exposure, which have been described for other CDK inhibitors. Interestingly, in terms of apoptosis, although the combination renders a clear increase, no potentiation of the ionising‐radiation‐induced apoptosis was observed. Mechanistically, inhibition of CDK12 by dinaciclib diminishes BRCA1 expression, which decreases homologous recombination (HR) and probably promotes the nonhomologous end joining repair process (NHEJ), which ultimately promotes the induction of ionising‐radiation‐associated cellular senescence in a TP53‐dependent manner, explaining the lack of effect observed in some experimental models. In conclusion, our report proposes a molecular mechanism, based on the signalling axis CDK12–BRCA1, involved in this newly identified therapeutic effect of dinaciclib, although other players implicated in HR should not be discarded. In addition, our data provide a rationale for more selective and personalised chemo/radiotherapy treatment according to the genetic background of the tumour.